Use the identity to find the following products.

(i)

(ii)

(iii)

(iv)

(v)

(vi)

(vii)

(i) Using Identity

In the given expression

On substituting these values in the above identity, we get

(ii) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(iii) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(iv) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(v) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(vi) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

(vii) Using Identity

In the given expression

On substituting these values in the above identity, we get

=

2